O-GlcNAcylation Is Involved in the Regulation of Stem Cell Markers Expression in Colon Cancer Cells - Fuentes-García, Gabriela; Castañeda-Patlán, M. Cristina; Vercoutter-Edouart, Anne-Sophie; Lefebvre, Tony; Robles-Flores, Martha (Frontiers in Endocrinology, 2019)
The dynamic O-linked-N-acetylglucosamine posttranslational modification of nucleocytoplasmic proteins has emerged as a key regulator of diverse cellular processes including several hallmarks of cancer. However, the role played by this modification in the establishment of CSC phenotype has not yet been defined. In this study we confirmed the previous reports showing that colon cancer cells exhibit higher O-GlcNAc basal levels than non-malignant cells, and investigated the role played by O-GlcNAcylation in the regulation of CSC phenotype. We found that the modification of O-GlcNAcylation levels by pharmacological inhibition of the O-GlcNAc-transferase enzyme that adds O-GlcNAc (OGT), but not of the enzyme that removes it (OGA), increased the expression of all stem cell markers tested in our colon malignant cell lines, and induced the appearance of a double positive (CD44+/CD133+) small stem cell-like subpopulation (which corresponded to 1-10%) that displayed very aggressive malignant phenotype such as increased clonogenicity and spheroid formation abilities in 3D culture. We reasoned that OGT inhibition would mimic in the tumor the presence of severe nutritional stress, and indeed, we demonstrated that nutritional stress reproduced in colon cancer cells the effects obtained with OGT inhibition. Thus, our data strongly suggests that stemness is regulated by HBP/O-GlcNAcylation nutrient sensing pathway, and that O-GlcNAc nutrient sensor represents an important survival mechanism in cancer cells under nutritional stressful conditions.